Surgical management of patients with colorectal cancer and simultaneous liver and lung metastases. Issue 6 (18th March 2015) - Andres, A.; Mentha, G.; Adam, R.; Gerstel, E.; Skipenko, O. G.; Barroso, E.; Lopez‐Ben, S.; Hubert, C.; Majno, P. E.; Toso, C.
<x xml:space="preserve">Abstract</x> Background The management of patients with colorectal cancer and simultaneously diagnosed liver and lung metastases (SLLM) remains controversial. Methods The LiverMetSurvey registry was interrogated for patients treated between 2000 and 2012 to assess outcomes after resection of SLLM, and the factors associated with survival. SLLM was defined as liver and lung metastases diagnosed 3 months or less apart. Survival was compared between patients with resected isolated liver metastases (group 1, control), those with resected liver and lung metastases (group 2), and patients with resected liver metastases and unresected (or unresectable) lung metastases (group 3). An Akaike test was used to select variables for assessment of survival adjusted for confounding variables. Results Group 1 (isolated liver metastases, hepatic resection alone) included 9185 patients, group 2 (resection of liver and lung metastases) 149 patients, and group 3 (resection of liver metastases, no resection of lung metastases) 285 patients. Ten variables differed significantly between groups and seven were included in the model for adjusted survival (age, number of liver metastases, synchronicity of liver metastases with primary tumour, carcinoembryonic antigen level, node status of the primary tumour, initial resectability of liver metastases and inclusion in group 3). Adjusted overall 5‐year survival was similar for groups 1 and 2 (51·5 and 44·5 per cent respectively), but worse for group 3 (14·3 per cent) (P = 0·001). Conclusion Patients who had resection of liver and lung metastases had similar overall survival to those who had undergone removal of isolated liver metastases.